Oncology clinical pharmacy services in Chinese hospitals. Issue 5 (18th June 2020) - Wang, Yanting; Dai, Yuanyuan; Lau, Alan H.; Yang, Jun; Chen, Wei; Li, Guohui
Abstract: In recent years, with an increasing number of oncology patients and continuous introduction of new antitumor drugs in China, the demand for oncology clinical pharmacy services is growing rapidly, which is both an opportunity and a challenge for clinical pharmacists. However, there have not been many reports about different types of oncology clinical pharmacy services in China. In this report, we have summarized different oncology clinical pharmacy services commonly practiced in Chinese hospitals based on our review of the literature and current practice in our hospital. We are reporting the training programs and the certification process for oncology clinical pharmacists, basic and advanced patient services, pharmacist‐driven and pharmacist‐participated guidelines/expert consensuses/books on oncology pharmacotherapy, as well as professional and public health education performed by pharmacists. Based on what we have observed, oncology clinical pharmacy services in China are relatively comprehensive, however, there are needs for expanding certain advanced pharmacy services. Increasing the time spent on clinical services, improving pharmacists' competency, and optimizing clinical pharmacy workflow and evaluation mechanisms are important for enhancing the value of oncology clinical pharmacists in China.